Comparison of diclofenac-emulgel local application with oral ibuprofen administration for the treatment of active interphalangeal hand joints osteoarthritis (Heberden and/or Bushar nodules) - J Zacher; K J Burger; L Farber; M Grave; H Abberger; K Bertsch (Научно-практическая ревматология, 2007)
Objective. To assess efficacy and tolerability of diclofenac-emulgel local application in comparison with oral ibuprofen administration for the treatment of active interphalangeal hand joints osteoarthritis (Heberden and/or Bushar nodules). Material and methods. 321 pts were randomized into two groups. Diclofenac-emulgel (active drug) and placebo ibuprofen tablets were administered in one of them, placebo diclofenac-emulgel and ibuprofen tablets (active drug) — in the other. Diclofenac was administered as 10 cm strip locally 4 times a day and 400 mg of ibuprofen were given 3 times a day. Frequency of improvement was used as the main outcome measure. Improvement was registered if pain on 100 mm visual analog scale decreased at least by 40%. Disease activity, pain at rest, pain at movement, morning stiffness, grip strength and quality of life were used as additional outcome measures. Results. To the end of treatment according to 5% lower equivalency limit local therapy was at least as effective as oral administration of ibuprofen (p=0,007). Administration of both treatment methods provided also comparable improvement of all additional outcome measures. Both treatment methods showed good tolerability but more pts with receiving ibuprofen experienced serious adverse events than those using diclofenac (9 and 4 pts respectively). There was also similar proportion of pts prematurely withdrawn due to side effects (n=21): 5 (3%) from them received diclofenac and 16 (10%) - ibuprofen. Similar ratio of adverse events attributed to study treatment was revealed. Such events were present in 2 pts using diclofenac and in 13 (8,3%) receiving ibuprofen. Most of these events applied to gastrointestinal tract (in 1 pt using diclofenac and in 8 pts receiving ibuprofen). Conclusion. Local treatment of active interphalangeal hand joints osteoarthritis (Heberden and/or Bushar nodules) with diclofenac is at least as effective as systemic administration of ibuprofen. Tolerability of local therapy with diclofenac probably exceeds tolerability of systemic treatment with ibuprofen. This applies to gastrointestinal safety and frequency of adverse events leading to treatment withdrawal.